Localizing Tungsten Single Atoms around Tungsten Nitride Nanoparticles for Efficient Oxygen Reduction Electrocatalysis in Metal–Air Batteries. Issue 28 (22nd June 2022) - Ma, Yuanyuan; Yu, Yong; Wang, Junhui; Lipton, Jason; Tan, Hui Ning; Zheng, Lirong; Yang, Tong; Liu, Zhaolin; Loh, Xian Jun; Pennycook, Stephen J.; Shen, Lei; Kou, Zongkui; et al.
Abstract: Combining isolated atomic active sites with those in nanoparticles for synergizing complex multistep catalysis is being actively pursued in the design of new electrocatalyst systems. However, these novel systems have been rarely studied due to the challenges with synthesis and analysis. Herein, a synergistically catalytic performance is demonstrated with a 0.89 V (vs reversible hydrogen electrode) onset potential in the four‐step oxygen reduction reaction (ORR) by localizing tungsten single atoms around tungsten nitride nanoparticles confined into nitrogen‐doped carbon (W SAs/WNNC). Through density functional theory calculations, it is shown that each of the active centers in the synergistic entity feature a specific potential‐determining step in their respective reaction pathway that can be merged to optimize the intermediate steps involving scaling relations on individual active centers. Impressively, the W SAs/WNNC as the air cathode in all‐solid‐state Zn‐air and Al‐air batteries demonstrate competitive durability and reversibility, despite the acknowledged low activity of W‐based catalyst toward the ORR. Abstract : A unique oversaturation method is employed to synthesize the ensemble catalysts, which comprises the tungsten single atoms and tungsten nitride nanoparticles. The synergistic binary system realizes an efficient four‐step process, oxygen reduction reaction, and gives good electrochemical performance when used as the electrodes for metal–air batteries.